Makna dan Filosofi Silat Perisai dalam Penyambutan Tamu Adat Melayu Riau - Septina Azzahwa; Risna Wulandari; Hikmah Kamilah; Fauziah Yenika Putri; Arwiwa Shofi Zetdafi; Pandu Wijaya; Dinda Lorenza Pratiwi; Elmustian Elmustian (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
Using the example of Lontiok's house on Belimbing Island, this article discusses the philosophy and meaning of "Silat Perisai" in welcoming Riau Malay guests. In Riau Malay tradition, welcoming guests is a form of respect that has cultural value and symbolism that is more than just a social formality. Silat Perisai, a traditional martial art, has philosophical meanings such as balance, protection and respect for guests besides functioning as physical exercise. This article explains how each movement in "Silat Shield" illustrates the principles of life respected by Malay society and its role in maintaining the honor and dignity of the community. Through the example of how the Lontiok Pulau Belimbing house welcomes guests, this article emphasizes the importance of "Silat Perisai" in building relationships and preserving Silat Perisai" to strengthen community relations and maintain Riau Malay cultural values. Silat shield in the life of Malay society. Silat, which is a martial arts style, is also a tradition that has close ties to the values ​​of community life. Silat itself is a reflection of the cultural values ​​of the area. Silat shield is a symbol of struggle and courage as well as a symbol of protection from all dangers. The fighters are taught skills in swordsmanship with the aim of having the skills to face threats from enemies who use similar weapons. Not only, perceived skills but also about personality. Some of the characteristics that are felt in Silat Shield are discipline and alertness. Not only that, but Silat Shield also emphasizes and prioritizes politeness, cleanliness and honesty. These values ​​are what continue to be maintained in the preservation of Silat Shield and of course this is not an easy thing.